Investigation of stress-strained state of complex parts after plasma surface hardening - Мазур, Владислав Александрович (Technology audit and production reserves, 2015)
The structure and properties of 35CML steel after plasma hardening was investigated, the mechanisms of influence upon formation of phase composition and residual stresses after surface treatment were revealed. It was found out that that residual micro-stresses at surface treatment of steel represented an algebraic sum of strain of two kinds – thermal strain, caused by uneven distribution of temperature along the part’s cross-section and structural strains, due to changes in volume resulting from phase transitions. Residual stresses in the surface layer were determined experimentally. Distribution of deformations in the specified part was simulated by applying of a source of highly concentrated energy. Recommendations were offered for the choice of the modes of plasma treatment. A part, made of the specified steel was hardened with application of designated modes and its geometric shape was controlled. Plasma surface treatment proved to be a promising method of increasing durability of engineering parts.